Analisis Diskursus Indonesia dalam Forum The Archipelagic Island and State (AIS) 2023 - Ridani, Syahri (Department of International Relations, Hasanuddin University, 2024)
The Archipelagic and Island States (AIS) Forum is a platform for island nations, regardless of their region, size, or level of development, aimed at addressing global challenges related to the sustainable use of marine resources, climate change resilience, marine pollution, emergency management, and the promotion of sustainable fisheries. Countries use international forums as the main instruments to tackle common issues in global politics. These forums are crucial for dialogue, where delegates meet and communicate through verbal and non-verbal language to express their concerns, share their views, and work towards reaching agreements. Initiated by Indonesia, the forum fosters new discourse among various international actors. This phenomenon raises the research question: How does Indonesia introduce and shape the discourse on marine development, climate change mitigation, and marine pollution management within the AIS Forum? The paper employs a constructivist paradigm to answer this research question, examining how Indonesia brings these issues into the AIS Forum, thereby creating a social construct within it. The research will utilize a qualitative, interpretative approach, employing data triangulation techniques that include interviews, literature reviews, and necessary documents. Consequently, the data sources will be secondary data. The Archipelagic and Island States (AIS) atau Forum Negara Kepulauan adalah sebuah platform bagi negara-negara kepulauan tanpa memandang wilayah, ukuran dan tingkat pembangunannya yang memiliki inisiasi global untuk mengatasi tantangan penggunanaan sumber daya laut untuk pertumbuhan ekonomi berkelanjutan, ketahanan terhadap perubahan iklim, polusi laut, manajemen darurat dan peningkatan perikanan berkelanjutan. Didalam forum ini terdapat aktor dalam hubungan internasional yang memiliki pengaruh dalam regional maupun internasional di bidang kemaritiman karena terdapat kesepakatan didalam forum tersebut yang di prakarsai oleh Indonesia sehingga memunculkan diskursus baru bagi beberapa aktor dalam hubungan internasional, oleh karena itu dari fenomena ini memunculkan pertanyaan penelitian bahwa bagaimana Indonesia membawa diskursus sektor pembangunan kelautan, mitigasi perubahan iklim dan penanggulangan pencemaran laut di forum AIS. Untuk menjawab pertanyaan penelitian ini, makalah ini akan menggunakan paradigma kontruktivisme. Teori ini akan melihat bagaimana Indonesia membawa diskursus ini ke dalam forum The Archipelagic and Island States (AIS) sehingga menciptakan kontruksi sosial di dalam forum AIS. Penelitian ini akan menggunakan metode penelitian kualitatif yang bersifat interpretatif dengan teknik pengumpulan data triangulasi dengan mengambil data kolaborasi wawancara, studi Pustaka dan juga dokumen yang diperlukan sehingga sumber data yang akan diperoleh ialah data sekunder.